This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: N ) = log a M-log a N where 0 &lt; a 6 = 1, M, N &gt; 0. Consequently, log a ( 1 M ) = log a 1-log a M =-log a M . Example 5 : Example 6 : 2 Example 7 : log a M = log a N M = N (0 &lt; a 6 = 1, M, N &gt; 0). 2 Change-of-Base Formula If 0 &lt; a 6 = 1, 0 &lt; b 6 = 1 and M &gt; 0, then log a M = log b M log b a (change from base a to base b ). Consequently, use the above formula to change to base e ( ln ) or base 10 ( log ): log a M = lnM lna . log a M = logM loga . Example 8 : Example 9 : 3...
View Full Document
- Spring '11
- Exponential Function, Natural logarithm, Logarithm, loga, Ms. Hoa Nguyen